국내 전문개인투자자의 투자 성향 분석: 엔젤투자 활성화 방안 모색 - 이인수; 이주연 (시스템엔지니어링학술지, 2024)
Amidst the challenges of the global economy, this paper examines the investment tendencies of professional angel investors, who provide venture capital and management consulting, and explores strategies to revitalize angel investment. According to the research findings, professional angel investors are generally older and more educated than regular angel investors, and they are concentrated in the metropolitan region. Additionally, their investment performance before and after registration remains similar, with investment amounts concentrated between 50 million and 100 million won. Their investment portfolios focus on ICT services, bio/medical, and distribution/service sectors. Based on these findings, policy and institutional support measures are required to revitalize angel investment, including easing registration requirements for professional angel investors, expanding tax benefits related to angel investment, strengthening the provision of information and education related to angel investment, and enhancing angel investment networking. This study is expected to contribute to the revitalization of the venture startup ecosystem and economic growth through the revitalization of angel investment.
Keywords: Angel investment; Professional angel investor; Investment tendencies; Venture capital; Early-stage financing